2012
DOI: 10.1007/s00431-012-1783-8
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin skin test in bacille Calmette–Guérin-vaccinated children: how should we interpret the results?

Abstract: A history of BCG vaccination at birth does not interfere with TST results in children >3 years old. Under 3 years of age, BCG does interfere with and may cause a false-positive TST result. In these cases, the use of interferon-gamma release assays (IGRAs) is recommended. If IGRAs are not available or when results are indeterminate, ignoring the antecedent of the vaccine is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 35 publications
2
18
1
1
Order By: Relevance
“…3,4 Therefore, the diagnosis of TB or latent tuberculosis infection (LTBI) often relies upon tuberculin skin test (TST), which has however several limitations, such as reduced sensitivity in patients with an impaired cellular immune response and poor specificity in Bacillus Calmétte-Guerin (BCG)-vaccinated individuals or in nontuberculous mycobacteria infections. [5][6][7] Furthermore, TST is reliant on correct administration and interpretation and it requires the patient's recall after 48-72 hours, with possible loss to follow up. 8 Recently, new diagnostic tests, based on the measurement of interferon-γ (IFN-γ) released by T cells in response to specific antigens of Mycobacterium tuberculosis (interferon-γ release assays, IGRAs), have become available.…”
mentioning
confidence: 99%
“…3,4 Therefore, the diagnosis of TB or latent tuberculosis infection (LTBI) often relies upon tuberculin skin test (TST), which has however several limitations, such as reduced sensitivity in patients with an impaired cellular immune response and poor specificity in Bacillus Calmétte-Guerin (BCG)-vaccinated individuals or in nontuberculous mycobacteria infections. [5][6][7] Furthermore, TST is reliant on correct administration and interpretation and it requires the patient's recall after 48-72 hours, with possible loss to follow up. 8 Recently, new diagnostic tests, based on the measurement of interferon-γ (IFN-γ) released by T cells in response to specific antigens of Mycobacterium tuberculosis (interferon-γ release assays, IGRAs), have become available.…”
mentioning
confidence: 99%
“…47 Piñeiro et al found that the vaccinated children in a cohort of children who had been adopted in, or had emigrated from highly endemic areas were at greater risk of a positive TST than those who had not been vaccinated (OR 2.35, 95% CI 1.32-4.21), but this only applied during the 3 y after vaccination. 48 Bozaykut et al found a significant difference in TST responses between vaccinated and unvaccinated children aged 1-6 years, without any variation between one age and another. 49 BCG vaccination is recommended in Italy for all TSTnegative newborns/breastfeeding infants aged <6 months coming from areas in which TB is highly endemic, or whose parents come from areas in which TB is highly endemic [I-B]; BCG vaccination is recommended in Italy for all TSTnegative newborns/breastfeeding children aged <6 months who have come into contact with a family member affected by active TB and in whom the presence of the disease has been excluded [I-B]; BCG vaccination is recommended in Italy for all TSTnegative children aged from 6 months to at least 5 y coming from areas in which TB is highly endemic, or whose parents come from areas in which TB is highly endemic [I-B]; BCG vaccination is recommended in Italy for all TSTnegative children aged from 6 months to at least 5 y who have come into contact with a family member affected by active TB [I-B]; previously vaccinated children should not receive a second vaccination [I-A]; before vaccinating a newborn, it is necessary to ascertain that the mother was screened for HIV during her pregnancy.…”
Section: Does Bcg Vaccination Affect Tst Responses?mentioning
confidence: 97%
“…44 However, many pediatric studies have not found any significant difference in the rates of TST positivity between vaccinated and unvaccinated children. 45 The bibliographical search identified 6 cohort studies that have evaluated the effect of BCG vaccine on TST responses, 27,29,[47][48][49] and recent studies comparing the TST and IGRA responses of vaccinated subjects have shown that BCG vaccination does affect TST positivity. 27,29,46 A multicentre study by .…”
Section: Does Bcg Vaccination Affect Tst Responses?mentioning
confidence: 99%
“…Sin embargo, la PT tiene sus limitaciones, como los resultados falsos positivos en pacientes que han sido infectados previamente por micobacterias no tuberculosas. Con todo, la mayor interferencia la encontramos en aquellas personas que han sido vacunadas con el bacilo Calmette-Gué rin (BCG) [2][3][4] . Los falsos positivos de la PT suponen tratar innecesariamente a pacientes que no está n realmente infectados, con el consiguiente riesgo potencial de toxicidad 5 .…”
Section: Introducció Nunclassified